The Impact of Screening and Partner Notification on Chlamydia Prevalence and Numbers of Infections Averted in the United States, 2000–2015: Evaluation of Epidemiologic Trends Using a Pair-Formation Transmission Model. Issue 3 (4th January 2019) - Rönn, Minttu M; Tuite, Ashleigh R; Menzies, Nicolas A; Wolf, Emory E; Gift, Thomas L; Chesson, Harrell W; Torrone, Elizabeth; Berruti, Andrés; Mazzola, Emanuele; Galer, Kara; Hsu, Katherine; Salomon, Joshua A
Abstract: Population-level effects of control strategies on the dynamics of Chlamydia trachomatis transmission are difficult to quantify. In this study, we calibrated a novel sex- and age-stratified pair-formation transmission model of chlamydial infection to epidemiologic data in the United States for 2000–2015. We used sex- and age-specific prevalence estimates from the National Health and Nutrition Examination Surveys, case report data from national chlamydia surveillance, and survey data from the Youth Risk Behavior Survey on the proportion of the sexually active population aged 15–18 years. We were able to reconcile national prevalence estimates and case report data by allowing for changes over time in screening coverage and reporting completeness. In retrospective analysis, chlamydia prevalence was estimated to be almost twice the current levels in the absence of screening and partner notification. Although chlamydia screening and partner notification were both found to reduce chlamydia burden, the relative magnitude of their estimated impacts varied in our sensitivity analyses. The variation in the model predictions highlights the need for further data collection and research to improve our understanding of the natural history of chlamydia and the pathways through which prevention strategies affect transmission dynamics.